Advancements in Pharmaceutical Compounding and Personalized Medicine: A Comprehensive Review on Enhancing Medication Adherence and Patient Engagement - Alsheikhahmed, Mohammed Ahmed; Altokes, Othmman Saad Othmman; Al Nafisah, Dina Abdulrahman; Alotaibi, Fares Ghaleb; Alnughaytir , Ibrahim Abdullahi; ALNUGHAYTHIR, ABDULRAHMAN ABDULLAH I; Alshammari, Shaluq Meshal; GHAZALI, FATMAH DIVA UDDIN; ALABDULWAHED, ABDULAZIZ ABDULRAHMAN; Alamri, Fawzi Mohammed; Aldawsari, Ahmed Barrak; Mashnafi, Gasim Mohamed Gasim; et al. (Journal of Ecohumanism, 2024)
Background: Medication adherence is a critical component of effective healthcare, yet non-adherence poses a significant public health challenge, leading to preventable morbidity and mortality. Factors influencing adherence include socioeconomic conditions, healthcare systems, and medication characteristics. This review explores advances in compounding pharmacy and personalized medicine as strategies to enhance medication adherence. Methods: This review synthesizes existing literature on medication adherence, focusing on the role of pharmaceutical compounding and personalized medicine. Key performance indicators (KPIs), 360-degree feedback, self-assessments, and surveys were employed to evaluate patient preferences and adherence rates related to compounded medications. Results: The findings indicate that orodispersible dosage forms significantly improve adherence compared to traditional medications. Additionally, the customization of medications through compounding addresses specific patient needs, particularly in pediatric and geriatric populations, enhancing overall treatment compliance. The review also highlights the necessity of a patient-centric approach in compounding practices to accommodate individual preferences and improve adherence rates. Conclusion: The integration of compounding pharmacy and personalized medicine represents a promising avenue for addressing the multifaceted issue of medication non-adherence. By tailoring medications to meet the unique needs of patients, healthcare providers can enhance patient engagement, satisfaction, and overall health outcomes. Future research should investigate the long-term impacts of these approaches on adherence and health outcomes across diverse patient populations.